Collaborative Study on Assays of Activated FIX (FIXa) On Behalf of the Factor VIII and Factor IX Subcommittee of the ISTH - Gray, Elaine; Walker, Dawn; Heath, Alan; Barrowcliffe, Trevor W (Thrombosis and Haemostasis, 1996)
A collaborative study has been organised by NIBSC to examine the performance of FIXa assays between laboratories, and to investigate the need for a standard. Ampoules of 3 materials, one monocomponent concentrate (coded C) and 2 different preparations of purified human FIXa (one proposed reference preparation, coded A and a test material coded B), have been assayed in 11 laboratories for FIXa using either the NIBSC method or a local method, with local standards (if available, coded D) to determine their potencies. The data showed high between assay variability; with the exception of one laboratory, most of the between assay variation expressed as %geometric coefficients of variation (gcv) were over 15%The interlaboratory gcv when preparation B was assayed against the local standard was over 1700%, suggesting that most of the local standards are poorly calibrated. The %gcv was improved to 80% when reference A was used as the standard. These data clearly show that an international reference standard for FIXa would help to standardise FIXa preparations and would also improve in house assays for FIXa. However, an accelerated degradation study has shown that reference A is not suitable as a long term standard and another material with suitable stabilisers has to be established as an international standard for FIXa.